The geographical and seasonal effects on the composition of marine microplastic and its microbial communities: The case study of Israel and Portugal - Marsay, Katherine S.; Ambrosino, Ana C.; Koucherov, Yuri; Davidov, Keren; Figueiredo, Neusa; Yakovenko, Iryna; Itzahri, Sheli; Martins, Marta; Sobral, Paula; Oren, Matan (Frontiers in Microbiology, 2023)
Floating microplastic debris are found in most marine environments around the world. Due to their low density and high durability, plastic polymers such as polyethylene, polypropylene and polystyrene serve as stable floating substrates for the colonization of diverse communities of marine organisms. Despite the high abundance of microplastic debris in the oceans, it is not clear how the geographical location and season affect the composition of marine microplastic and its bacterial microbiome in the natural environment. To address this question, microplastic debris were collected from the sea surface near estuaries in the Mediterranean Sea (Israel) and in the Atlantic Ocean (Portugal) during summer and winter of 2021. The microplastic physical characteristics, including shape, color and polymer composition, were analyzed and the taxonomic structure of the microplastic bacterial microbiome was characterized using a high-resolution metabarcoding pipeline. Our results, supported by previously published data, suggest that the plastisphere is a highly diverse ecosystem which is strongly shaped by spatial and temporal environmental factors. The geographical location had the highest impact on the plastisphere physical characteristics and its microbiome composition, followed by the season. Our metabarcoding analysis showed great variability between the different marine environments with a very limited microbiome ‘core’. This notion further emphasizes the importance of plastisphere studies in different geographical locations and/or seasons for the characterization of the plastisphere and the identification of plastic-associated species.